Berkreasi Dengan Aplikasi Spread Sheet - Ferdinando Solissa; Putu Anggreyani Widya; Margaretha Turot; Roberthair Suripatty; La Ode Ghondohi; Irwan Soulisa; Intan Sampelobo (CV. ITTC INDONESIA, 2025)
The Community Service (PKM) activity carried out by the Accounting Study Program of Victory University Sorong was the second activity at the request of the Principal of SMA Negeri 2 Sorong Regency in the implementation of the Tridharma of Higher Education, specifically to introduce and train the use of Microsoft Excel (Spreadsheet) applications to students of SMA Negeri 2 Sorong Regency. The results of this PKM activity A total of 28 participants were selected by the school based on their interests and basic competencies in the field of taxation. During the activity, participants showed high participation and enthusiasm, both in theory and practice sessions. This activity also received full support from the school, including the principal and accompanying teachers, who helped ensure the smooth implementation. In general, this PKM activity ran smoothly. This was achieved thanks to the support of the Dean and Lecturers of Victory University Sorong, the Economics and Business Study Program and Teachers of SMA Negeri 2 Sorong Regency. As well as the cooperation of the TEAM.